2021
DOI: 10.2967/jnumed.120.255745
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response and Dose–Toxicity Relationships for Glass 90Y Radioembolization in Patients with Liver Metastases from Colorectal Cancer

Abstract: Purpose Radioembolization based on personalized treatment planning requires established doseresponse and dose-toxicity relationships. The aim of this study was to investigate dose-response and dose-toxicity relationships in patients with colorectal liver metastases (CRLM) treated with glass yttrium-90 ( 90 Y)-microspheres. Methods All CRLM patients treated with glass 90 Y-microspheres in our institution were retrospectively analyzed. The tumor-absorbed dose was calculated for each measurable metastasis (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…In fact, for HCC and in mCRC, the tumor response is strictly related to the tumor-absorbed dose, while the liver toxicity should be limited by preliminary assessment of the healthy liver-absorbed dose, which should not exceed certain thresholds [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for HCC and in mCRC, the tumor response is strictly related to the tumor-absorbed dose, while the liver toxicity should be limited by preliminary assessment of the healthy liver-absorbed dose, which should not exceed certain thresholds [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study conducted between 2011–2014 with 30 patients, which used the BSA model for treatment planning, reported a conservative estimate of at least 40–60 Gy tumor dose was predictive of metabolic response [ 25 ], and another study found 50 Gy (using modified BSA method) as threshold to achieve objective response [ 26 ], both using resin microspheres. A more recent 2021 retrospective study with 31 patients using glass microspheres found that median TD for complete responders was 196 Gy versus 177 Gy for partial responders [ 27 ]. This higher TD compared to our findings of 100 Gy can most likely be explained by their use of glass microspheres compared to our use of resin microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…The applied tumor dose is decisive for patient outcomes in RE. Previous studies have demonstrated the correlation of survival and absorbed tumor dose [ 6 , 7 , 8 , 9 , 10 ]. In addition, variations in response rates after RE indicate a medical need for optimizing dose prescriptions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%